GCHQ Demonstration, Cheltenham, 1989 (1989)
1989 1960-2000 "GCHQ Demonstration, Cheltenham, 1989" [T0556.jpg], 1989 In January 1984, civil service staff working at the Government Communications Headquarters in Cheltenham were banned from holding trade union membership. The International Labour Organisation condemned the ban but, after a long legal battle, the House of lords decided for the Government and the first sackings of trade union members started in November 1988. On 28 January 1989, over 10,000 people marched through Cheltenham to protest the continuation of the ban.